2016
DOI: 10.5137/1019-5149.jtn.18901-16.1
|View full text |Cite
|
Sign up to set email alerts
|

2-methoxyestradiol inhibits intracerebral hemorrhage-induced angiogenesis in rats

Abstract: HIF-1? inhibitor, 2ME2, inhibited post-ICH angiogenesis by suppressing HIF-1? expression, thus exerting detrimental effects in ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The adjacent tissues and blood vessels are also subject to the ischemic stress after cerebral hemorrhage, which further aggravates brain damage. A recent finding indicate that HIF-1α plays a critical role in ICH-induced angiogenesis [ 54 ]. Promoting cerebral angiogenesis and neurogenesis is also an important strategy to ameliorate brain functional damage after ICH.…”
Section: Mechanism Of Msc-evs/exo In the Treatment Of Ichmentioning
confidence: 99%
“…The adjacent tissues and blood vessels are also subject to the ischemic stress after cerebral hemorrhage, which further aggravates brain damage. A recent finding indicate that HIF-1α plays a critical role in ICH-induced angiogenesis [ 54 ]. Promoting cerebral angiogenesis and neurogenesis is also an important strategy to ameliorate brain functional damage after ICH.…”
Section: Mechanism Of Msc-evs/exo In the Treatment Of Ichmentioning
confidence: 99%
“…As HIF‐1α target genes mediate angiogenesis, HIF‐1α inhibitors or silencing proved detrimental for new vessel formation after experimental intracerebral hemorrhage and cerebral ischemia (Li, Zhou, et al, ; Liu et al, ). In particular, HIF deficiency reduces VEGF‐A, Flk‐1, Neuropilin‐1 (NRP1), Delta‐like 4 (Dll4), CXCL12, and HMGB1 in the ischemic brains, among others affecting bone marrow endothelial progenitor cells homing and sprouting (Liu et al, ).…”
Section: Protective Role Of Hif In Cells Of the Cnsmentioning
confidence: 99%
“…W e read the article with great interest by Li et al entitled "2-Methoxyestradiol Inhibits Intracerebral Hemorrhage-Induced Angiogenesis in Rats" (6). In this paper, Li et al reported that the Hypoxia-inducible factor-1α (HIF-1α) inhibitor, 2-Methoxyestradiol (2ME2) impaired postintracerebral hemorrhage (ICH) angiogenesis and functional recovery and again in this paper the authors consider that HIF-1α may have a protective effect against ICH-induced damage.…”
Section: To the Editor;mentioning
confidence: 99%